GRAMMATICAL CATEGORIES OF NOUN - Janabayeva Nilufar Yergeshbayevna (PEDAGOGS, 2024)
In any language, nouns play a crucial role in communication, providing the foundation upon which sentences are constructed. This article discusses the grammatical categories of nouns.